2013
DOI: 10.1136/bmjopen-2013-002985
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of paid malpractice claims settled in and out of court in the USA: a retrospective analysis

Abstract: ObjectiveAn analysis of paid malpractice claims judged in court compared with those settled out of court may help explain perceptions of malpractice risk.DesignA retrospective analysis and cross-sectional comparison of malpractice claims. Evaluated trends in the number and proportion of paid claims, and mean payment amount by resolution type; identified patient, physician and claim characteristics associated with each resolution type. Examined the effects of resolution type on payment amount and time to claim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
1
15
2
Order By: Relevance
“…The duration of the settled claims in Thailand is not different from both China and the United States, which take about a year (Li et al, ; Studdert et al, ). Moreover, many studies have shown that the payments for claims settled out of court are lower than the claims judged in court (Rubin & Bishop, ). In the United States, the average payment for settlements has been approximately 1.7–2.4 times lower than judgements (Chandra, Nundy, & Seabury, ).…”
Section: Discussionmentioning
confidence: 99%
“…The duration of the settled claims in Thailand is not different from both China and the United States, which take about a year (Li et al, ; Studdert et al, ). Moreover, many studies have shown that the payments for claims settled out of court are lower than the claims judged in court (Rubin & Bishop, ). In the United States, the average payment for settlements has been approximately 1.7–2.4 times lower than judgements (Chandra, Nundy, & Seabury, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, several limitations of this study should be noted. First, although we used the largest claims database in Japan (similar to previous studies [12,29,32,33]), the data were not nationally representative of all malpractice claims. Second, there are no existing data on the frequency with which adverse events lead to malpractice claims in Japan.…”
Section: Plos Onementioning
confidence: 99%
“…Medical lawsuits are time-consuming and economically and psychologically burdensome. Several epidemiological and observational studies of the frequency of malpractice claims and the magnitude of awarded compensation indicate that diagnostic errors are a significant cause of medical liti- gation (5,(8)(9)(10)(11)(12). In general, it is difficult to estimate the actual frequency of errors from epidemiological studies' data of medical litigation because of selection bias in the trial process and in settlements.…”
Section: Introductionmentioning
confidence: 99%